The impact of internal migration to Khartoum state on the demand of Education and Health services (1992- 2008) - Abdelfarag, Nagla Osman (Journal of Economic, Administrative and Legal Sciences, 2019)
The research aimed to study the effect of internal migration to Khartoum on the demand on health and education services. The historical، analytical، and descriptive approaches were followed. The results showed that there are main causes of migration such as attending university education and having access to good health services. The number of basic level students rises to 1.5%، the schools increase at12.8%، 3.6% consequently between 2006- 2005، 2007- 2006، while the teachers number reaches 13.2%. Hospitals، centers، primary health units، blood banks and radiology units increase to 5.1%، 2.7%، 11.6%، 19%، 5.7% in 2005 comparing with 2004. The research has recommended encouraging investment in the pushing areas so as to create jobs opportunities and encouraging the private sectors. Another recommendation is to establish at least one governmental university in each administrative area and encourage establishing private universities and colleges so as to minimize migration for university education. It is also، recommended to improve the health services in the pushing areas to minimize the rate of migration to Khartoum.
Keywords: immigration; demand; supply; services; health; education